The Role of Timorese Women in Food Management - Puspita, Dhanang (Komunitas, 2017)
Timorese people have made gender segregation for several things such as; sex, traditional house and job. Timorese women are identical to round houses (ume kbubu), where inside the house, the women spend their time and activities. Timorese women play an important role in ume kbubu, one of which is the management of food. The purpose of this research is to investigate the role of Timorese women in food management. This research was conducted in Binaus Village, Molo Tengah District, South Central Timor Regency, West Nusa Tenggara Province. This research employed qualitative descriptive method from observation and interview. Timorese entitlement receives rights and responsibilities related to food management. They will arrange all streams of incoming and outgoing food. The conclusion of this research is that Timorese women have full control over family food management.